Studying disability arts and culture : an introduction - Kuppers, Petra (Houndmills, Basingstoke [England] ; Palgrave Macmillan, 2014)
"In this practical introduction to the study of Disability Arts and Culture, Petra Kuppers draws on a wide range of examples, exercises and activities to introduce the key artists and theoretical concepts in this diverse field. Comprehensive and accessible, this is an essential handbook for anyone interested in the Disabled body in performance"--
Machine generated contents note: -- List of Illustrations -- Acknowledgements -- Preface -- PART I -- 1. Setting Up -- 2. Languages of Disability -- 3. Discourses of Disability -- 4. Embodiment/Enmindment: Processes of Living -- 5. Disability Culture -- PART II -- 6. Life in the Institution: Discourses at Work and at Play -- 7. Freak Shows and the Theatre -- 8. Disabled Dance and Dancerly Bodies -- 9. Superheroes and the Lure of Disability -- 10. Looking at Autism -- 11. Classroom Activism and Resources -- 12. Appendix: For Teachers -- Bibliography -- Index.
Includes bibliographical references (pages 174-180).
Keywords: People with disabilities and the arts; People with disabilities and the performing arts; Arts and society